IMPLEMENTATION OF STRATEGY MANAGEMENT FOR FOREIGN LANGUAGE LEARNING PROGRAMS IN ONLINE COURSE INSTITUTIONS - Sabilla Setia Wida; Muassomah; Nuril Mufidah (Universitas PGRI Palembang, 2023)
In the field of education, management plays a critical role in ensuring the caliber of educational initiatives. The secret to making educational institutions more competitive is strategic management, which also establishes the degree of program implementation success. This study is to examine how strategic management is applied in Arabic language learning programs at online learning institutions, with a focus on the @marhaban.academy institution's use of the Instagram platform. This study employs descriptive approaches in a qualitative manner. Comprehensive interviews, observation, and documentation were used to gather data. Three steps make up the employed data analysis technique: data reduction, data display, and conclusion drafting. The study's findings indicate that the @marhaban.academy strategy is being implemented in the Arabic language learning program through the following methods: 1) environmental analysis using the question box feature to gauge interest from language learners; 2) setting strategic goals using the institution's vision and mission; 3) identifying the organizational structure made up of a teaching team, marketing team, editorial team, and chairman; 4) creating a content strategy using the story feature to create mufrodat quizzes; and 5) learning through Arabic language cartoon films on Instagram.